Christian America and the Kingdom of God White Christian nationalism from the Puritans through January 6, 2021 - Hughes, Richard T. 1943-; Littlefield, Christina L.; Balmer, Randall Herbert 1954- (Urbana Chicago Springfield University of Illinois Press, 2025)
"The myth of a Christian America fuels a powerful political force sure of its moral superiority and intent on implementing a Christian nationalist agenda. Richard T. Hughes and Christina Littlefield draw on discussions of civil religion and forms of nationalism to explore the complex legal and cultural arguments for a Christian America. The authors also provide an in-depth examination of the Bible's words on the "chosen nation" and "kingdom of God" that Christian nationalists quote to support the idea of the US as a Christian nation. A timely new edition of the acclaimed work, Christian America and the Kingdom of God spotlights how the centuries-long pursuit of a Christian America has bred an aggressive white Christian nationalism that twists faith, unleashes unchristian behavior, and threatens the nation"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Christianity and politics -- United States; Kingdom of God -- Political aspects -- United States; Particularism (Theology) -- Political aspects -- United States; Kingdom of God -- Biblical teaching; Particularism (Theology) -- Biblical teaching